Genome-wide identification and expression profiling of B3 transcription factor genes in Populus alba × Populus glandulosa - Wei, Mingke; Li, Hui; Wang, Qiao; Liu, Rui; Yang, Linxi; Li, Quanzi (Frontiers in Plant Science, 2023)
B3-domain containing transcription factors (TFs) are well known to play important roles in various developmental processes, including embryogenesis, seed germination, etc. Characterizations and functional studies of the B3 TF superfamily in poplar are still limited, especially on their roles in wood formation. In this study, we conducted comprehensive bioinformatics and expression analysis of B3 TF genes in Populus alba × Populus glandulosa. A total of 160 B3 TF genes were identified in the genome of this hybrid poplar, and their chromosomal locations, syntenic relationships, gene structures, and promoter cis-acting elements were analyzed. Through domain structure and phylogenetic relationship analyses, these proteins were classified into four families LAV, RAV, ARF, and REM. Domain and conservation analyses revealed different gene numbers and different DNA-binding domains among families. Syntenic relationship analysis suggested that approximately 87% of the genes resulted from genome duplication (segmental or tandem), contributing to the expansion of the B3 family in P. alba × P. glandulosa. Phylogeny in seven species revealed the evolutionary relationship of B3 TF genes across different species. B3 domains among the eighteen proteins that were highly expressed in differentiating xylem had a high synteny, suggesting a common ancestor for these seven species. We performed co-expression analysis on the representative genes in two different ages of poplar, followed by pathways analysis. Among those genes co-expressed with four B3 genes, 14 were involved in lignin synthases and secondary cell walls biosynthesis, including PagCOMT2, PagCAD1, PagCCR2, PagCAD1, PagCCoAOMT1, PagSND2, and PagNST1. Our results provide valuable information for the B3 TF family in poplar and show the potential of B3 TF genes in engineering to improve wood properties.